Visible-broadband Localized Vector Vortex Beam Generator with a Multi-structure-composited Meta-surface - Zhuo Yang; Dengfeng Kuang (Nanomaterials, 2019)
We demonstrate a vortex beam generator meta-surface that consists of silver structures and graphene layers. The miniature material is just a few microns in size and the working part is only a few hundred nanometers thick. With the incidence of the linearly polarized beam, the meta-surface generates high-localized vector vortex beam with a high proportion of the longitudinal component. Being compared with the constituent part of the meta-surface, the multi-structure-combined meta-surface increases the localization by 250% and the longitudinal component proportion by 200%. Moreover, the above artificial material can generate vortex beams in broadband within the visible light range. These novel optical properties have the potential to improve the precision and sensitivity of nanoparticle manipulation. The study serves as a foundation in optical miniaturization and integration, nanoparticle manipulation, high-efficiency optical and quantum communication, and light-driven micro-tools.